Interrelations of Synthesis Method, Polyethylene Glycol Coating, Physico-Chemical Characteristics, and Antimicrobial Activity of Silver Nanoparticles - Amirah Shafilla Mohamad Kasim; Arbakariya Bin Ariff; Rosfarizan Mohamad; Fadzlie Wong Faizal Wong (Nanomaterials, 2020)
Silver nanoparticles (AgNPs) have been found to have extensive biomedical and biological applications. They can be synthesised using chemical and biological methods, and coated by polymer to enhance their stability. Hence, the changes in the physico-chemical characteristics of AgNPs must be scrutinised due to their importance for biological activity. The UV-Visible absorption spectra of polyethylene glycol (PEG) -coated AgNPs displayed a distinctive narrow peak compared to uncoated AgNPs. In addition, High-Resolution Transmission Electron Microscopy analysis revealed that the shapes of all AgNPs, were predominantly spherical, triangular, and rod-shaped. Fourier-Transform Infrared Spectroscopy analysis further confirmed the role of PEG molecules in the reduction and stabilisation of the AgNPs. Moreover, dynamic light scattering analysis also revealed that the polydispersity index values of PEG-coated AgNPs were lower than the uncoated AgNPs, implying a more uniform size distribution. Furthermore, the uncoated and PEG-coated biologically synthesised AgNPs demonstrated antagonisms activities towards tested pathogenic bacteria, whereas no antagonism activity was detected for the chemically synthesised AgNPs. Overall, generalisation on the interrelations of synthesis methods, PEG coating, characteristics, and antimicrobial activity of AgNPs were established in this study.